2022
DOI: 10.1111/jpc.15924
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory spectrum of inborn errors of immunity in Egypt: Five years of experience at a tertiary care university hospital

Abstract: The recognition and diagnosis of primary immunodeficiency disorders (PIDs) is challenging in developing countries. This study aimed to describe the features of PID patients in a tertiary care setting in Egypt and analyse the distribution, clinical features and outcome of PID among paediatric patients. Methods: This cross-sectional retrospective study was conducted between January 2016 and January 2021, to evaluate all paediatric patients aged below 18 years with PID that were diagnosed according to the Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(121 reference statements)
1
2
0
Order By: Relevance
“…Consanguinity showed high rates between our cases (58.2%) and this was near to an Egyptian study on PID patients 2022 (20) the rate was 52.8% .Other studies on PID patients showed also this high rate for example, a study in IRAN on PID (21) revealed consanguineous marriage in (60.1%) another study in Oman documented consanguinity in 76 % of patients (10) the same in sauidi Arabia (Al-In our study consanguinity rate was higher in rural areas than urban areas (76%) versus (23%) respectively and this is similar to most studies on Egyptian population either in the past (22) and recent studies (23) and this explain the higher rate of PID in rural areas than urban areas 70.9% vs 29.1%. the same in sauidi Arabia (13) 75% and Tunisia (9) (46%).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consanguinity showed high rates between our cases (58.2%) and this was near to an Egyptian study on PID patients 2022 (20) the rate was 52.8% .Other studies on PID patients showed also this high rate for example, a study in IRAN on PID (21) revealed consanguineous marriage in (60.1%) another study in Oman documented consanguinity in 76 % of patients (10) the same in sauidi Arabia (Al-In our study consanguinity rate was higher in rural areas than urban areas (76%) versus (23%) respectively and this is similar to most studies on Egyptian population either in the past (22) and recent studies (23) and this explain the higher rate of PID in rural areas than urban areas 70.9% vs 29.1%. the same in sauidi Arabia (13) 75% and Tunisia (9) (46%).…”
Section: Discussionsupporting
confidence: 67%
“…By comparison with other studies, in two Egyptian studies on PID patients (32,20) the mortality rate was 23.4% and 24.5%, respectively. Nonetheless, low death rates were observed in France (26) was (3.5%), Mexico (18) (6.82%), Saudi Arabia (13) (10.3%) and the United Kingdom (24) (13%).…”
Section: Discussionmentioning
confidence: 65%
“…Our diagnosis spectrum was also different than other studies published from Egypt. Almalky and his colleagues reported that CID with syndromic features followed by antibody defects were the comments categories diagnosed among their cohort [ 31 ]. Another study from Egypt reported that antibody defects and combined immunodeficiencies were the highest categories diagnosed [ 32 ].…”
Section: Discussionmentioning
confidence: 99%